Response to COVID-19 in the Central African Republic: Coping Strategies Combined With China's Experience - Qiheng Gou; Fubin Zhu; Keqi Xie; Yiping Li; Yuxin Xie; Yuxin Xie (Frontiers Media S.A., 2022)
Objectives: The weak health system, domestic political unrest, poverty, and many other factors in the Central African Republic (CAR) have left the country underprepared for the COVID-19 pandemic, resulting in a greater health threat to the entire country. Rapid measures must therefore be taken to prevent the further spread of COVID-19.Methods: This work encompassed a review of relevant literature. We aim to analyze how far Chinese COVID measures can be transferred to the context of the CAR.Results: We argue that the measure that the CAR can learn from China's success is the involvement of community workers and that greater investment in this model may be the optimal solution. Help from the international community is urgently needed.Conclusion: The CAR can benefit from China's successful experience in fighting the epidemic, but the disparity in the combined power of the two countries does not allow for simple replication of China's strategy.